Vietnam - The Role of Postal Networks in Expanding Access to Financial Services Country case : Vietnam's postal finance services - World Bank (Washington, DC, 2013)
This paper discusses the role of the postal network in expanding access to financial services in Vietnam. It reviews the public postal operator within the postal sector and within the broader context of the communications sector. The roles of the Vietnam postal network and post bank are also reviewed from the perspective of the financial sector development, with particular focus on payments systems development and micro finance. While this country case on Vietnam can stand alone, it is an integral part of this large study of the potential of postal networks to coordinate with financial service providers in 7 countries (Egypt, Kazakhstan, Namibia, Romania, Sri Lanka, Uganda, and Vietnam) and 5 regions (Africa, Asia, Eastern Europe and Central Asia, Latin America and the Caribbean, and the Middle East and Northern Africa). Five years after its introduction, the Vietnamese Postal Savings Corporation (VPSC) can look back on an impressive record of successes. With its 920 post offices (of 3,000), VPSC operates the second-largest financial service network in the country. It developed as a channel for mobilizing small household deposits, nearly 400,000 individuals keep accounts with the VPSC, and it has mobilized about 1 percent of the nation's savings. It has also pioneered modern cashless payment services, and provides payroll and card-based services. The next step in its development is the integration of the postal payment services into its operations. However, after an initially fast growth track, VPSC currently faces increasing stagnation in its growth, mainly due to government limitations on its institutional and regulatory framework. Changes are required to enable sustainable growth of VPSC and including the post offices in its provision of low-threshold access to basic financial services.